Echoes of the dreamtime : Australian aboriginal myths in the paintings of Ainslie Roberts - Roberts, Ainslie, 1911-1993; Roberts, Melva Jean. (Melbourne : J.M. Dent, 1988)
Retelling of Aboriginal legends concerning creation, birth, death, animals, etc., combined with the paintings of Ainslie Roberts.
Includes bibliographical references.
Keywords: Roberts, Ainslie, -- 1911-1993; Mythology, Aboriginal Australian, in art; Mythology, Aboriginal Australian; Animals; Stories and motifs - Creation / Cosmology; Reproduction - Childbirth; Australia